Legal Protection Of Participants Applications For Land Certificates Through Complete Systematic Land Registration (PTSL) In Blora Regency - Sriyono Sriyono; Amin Purnawan (Jurnal Daulat Hukum, 2020)
The ATR / BPN Ministry launched a Systematic Complete Land Registration (PTSL) as a National Priority Program. This program is intended for middle to low income groups who can have land rights certificates at a low cost, as well as to provide legal certainty guarantees to holders of land rights. One important thing that must be considered in the implementation of PTSL is the availability of laws and regulations that protect the PTSL process and products. The formulation of the problem in this research is what is the form of legal protection for participants in a complete systematic land registration program (PTSL) in Blora Regency. The method used is sociological juridical. The specifications in this study are descriptive analysis. The data used for this study are primary and secondary data obtained from the field observation, interviews, and literature study methods. Based on the research concluded with the Regulation of the Minister of Agrarian Spatial Planning / Head of the National Land Agency Number 6 of 2018 On Complete Systematic Land Registration if there are parties who feel their interests are harmed, they can submit an objection to the official who issues the discretionary decision.Keywords: Legal Protection; Land Rights Certificate; Complete Systematic Land Registration.